Ritual Tasyakuran Pernikahan terhadap Roh pada Masyarakat Jawa di Desa Sidodadi Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan - Fathanah, Yulia (UIN Sumatera Utara, 2024)
Tasyakuran is defined as a belief that originates from a teaching that has been passed down from one age to another which is monitored and preserved. Naturally, religious beliefs, doctrines or practices have an impact on the Tasyakuran ritual. Ways of understanding tradition have varied over time. Tasyakuran comes in various forms and is performed at certain times, including weddings. Of course, weddings are held in different ways in each region, and Siodadi Village in Kampung Rakyat District, Labuhan Batu Selatan Regency, is no exception. This study aims to find out the Tasyakuran custom or the practice of giving at a wedding in Sidodadi City, to understand the importance, reasons and values contained in this practice and the things that make this custom exist today. In this research, field research, qualitative research method, is used to get the right information by following this tradition. Data collection techniques through interviews, observation, and documentation. Although the examination used in this study is an enlightening investigation, it tends to describe and interpret important exploratory data. The research findings are as follows: In Sidodadi Village, the practice of giving offerings at wedding ceremonies still exist, but some of them have taken on new meanings and adapted to the acceptance of Islamic teachings by society. 2). Tasyakuran means